Prevalence of hypertension in Shenzhen, China: a population-based, cross-sectional study - Ke Peng; Ji Peng; Yirong Wang; Weicong Cai; Lin Lei; Rencheng Zhao; Fangjiang Liu; Kaihao Lin; Fengzhu Xie (BMJ Open)
Objective Hypertension (HTN) is an important public health issue worldwide, associated with the rapid economic development and urbanisation over the last decades. This is especially the case in Shenzhen, which has benefited greatly from the reform and opening-up policies. However, there is limited information on the epidemiology of HTN in this region. This study was designed to investigate the prevalence, awareness, treatment and control of HTN and the associated factors among adult residents in Shenzhen, China.Design Population-based, cross-sectional study.Participants Through the multistage stratified random sampling method, a representative sample of 10 043 urban population aged ≥18 years were selected. Three consecutive blood pressure (BP) readings were measured after resting for a 5 min seat by trained staff and HTN was defined as mean systolic BP ≥140 mm Hg and/or diastolic BP ≥90 mm Hg and/or self-reported current use of antihypertensive drugs. Participants were interviewed using a structured questionnaire. Anthropometric details, BP, blood and urine samples were also collected.Primary outcome measure Prevalence of HTN.Results Overall, the weighted prevalence of HTN among residents in Shenzhen was 19.2% (95% CI 18.5 to 20.0). Among patients with HTN, 55.0% (95% CI 52.9 to 57.1) were aware of their condition and 44.9% (95% CI 42.8 to 47.1) were taking antihypertensive medications, but only 21.7% (95% CI 20.0 to 23.5) achieved BP control. Among those who knew their HTN, 81.7% (95% CI 79.3 to 83.8) were under treatment and 48.3% (95% CI 45.1 to 51.5) were controlled among those with treated HTN. Male, older age, lower educational level, overweight and obesity, family history of HTN, tobacco smoking, alcohol intake, diabetes mellitus, dyslipidaemia and high uric acid were associated with HTN.Conclusions HTN is a major public health concern in Shenzhen, which has low awareness, treatment and control rates, and is associated with several risk factors. Effective multifaceted implementation strategies are highly needed to combat the emerging burden of HTN.